THE ESCAZU AGREEMENT: CHALLENGES AND OPPORTUNITIES FOR ITS IMPLEMENTATION IN PERU - Peruana de Derecho Internacional, Sociedad (2020)
The benefits of the implementation of a treaty are measured according to the capacity of aState to comply with its provisions effectively. The Regional Agreement onAccess to Information, Public Participation and Access to Justice in MattersEnvironmental in Latin America and the Caribbean - known as the Escazú Agreement - regulatesrights linked to human and environmental rights. Considering that many ofThe countries of the Latin American and Caribbean region subject their economic development toindustries that are in direct conflict with the rights protected by the agreement, it is worthreview whether your application can guarantee compliance with these rights without harmingestablished economic processes. In order to support these ideas, this article will beginwith a brief explanation of the content of the Escazú Agreement, to later study theapplication of the same from the point of view of international law, where thecontingencies related to supranational jurisdiction, the implications regarding sovereignty,and the commitments and obligations that the States Parties would have to assume. Finally I knowwill address aspects related to the effect that its application will have in national law, such asare the possible changes in the legislation and the interpretative scope of some of itsbeginning.